2010
DOI: 10.3390/rs2092148
|View full text |Cite
|
Sign up to set email alerts
|

What Do Observational Datasets Say about Modeled Tropospheric Temperature Trends since 1979?

Abstract: Updated tropical lower tropospheric temperature datasets covering the period 1979-2009 are presented and assessed for accuracy based upon recent publications and several analyses conducted here. We conclude that the lower tropospheric temperature (T LT ) trend over these 31 years is +0.09 ± 0.03 °C decade −1 . Given that the surface temperature (T sfc ) trends from three different groups agree extremely closely among themselves (~ +0.12 °C decade −1 ) this indicates that the -scaling ratio‖ (SR, or ratio of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
1
34
1
1
Order By: Relevance
“…These data have been interpreted as indicating too little warming trend in the upper compared to the lower troposphere (Fu et al 2011, Po-Chedley andFu 2012) and one satellite product shows less warming in the atmosphere than at the surface (Christy et al 2010). Caution is warranted however because the satellites suffer from uncertain changes over time in calibration and other inhomogeneities, exacerbated by the manipulations of the data necessary to extract the signals of concern here (CCSP 2006).…”
Section: Introductionmentioning
confidence: 98%
“…These data have been interpreted as indicating too little warming trend in the upper compared to the lower troposphere (Fu et al 2011, Po-Chedley andFu 2012) and one satellite product shows less warming in the atmosphere than at the surface (Christy et al 2010). Caution is warranted however because the satellites suffer from uncertain changes over time in calibration and other inhomogeneities, exacerbated by the manipulations of the data necessary to extract the signals of concern here (CCSP 2006).…”
Section: Introductionmentioning
confidence: 98%
“…compared MSU measurements with the results from a subset of a single radiosonde data set and concluded that the University of Alabama, Huntsville (UAH) satellite data set was more accurate than the RSS data. They focused on trends in the data set differences over 5‐year and 10 year periods, and on a limited analysis period Christy et al [2010] Christy et al [2007]…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, however, there are also studies that question the accuracy or even conclusions of this report, see e.g. [20], [65], [37]. As a scientist, and lay-man in this field, the overall impression is that we start of to see some global contours and factors impacting each other, but that an in-depth understanding of the material is far from complete.…”
Section: Some Private Considerations 21 Considerations About Climatementioning
confidence: 92%